THE MAIN FACTORS OF INFORMATION CULTURE - Yuldoshev Utkir Zhumakuzievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article examines the main factors of information culture of schoolchildren in the context of glabolization and digitalization of education and methodological problems of information culture.